2014
DOI: 10.1158/1078-0432.ccr-13-3426
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Paracrine Signaling Activates Stromal Cells to Promote Perineural Invasion in Pancreatic Cancer

Abstract: Purpose: Pancreatic cancer is characterized by stromal desmoplasia and perineural invasion (PNI). We sought to explore the contribution of pancreatic stellate cells (PSC) activated by paracrine Sonic Hedgehog (SHH) in pancreatic cancer PNI and progression.Experimental Design: In this study, the expression dynamics of SHH were examined via immunohistochemistry, real-time PCR, and Western blot analysis in a cohort of carcinomatous and nonneoplastic pancreatic tissues and cells. A series of in vivo and in vitro a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 45 publications
(45 reference statements)
5
113
0
Order By: Relevance
“…Since neoplasms and embryonic development share similar molecular signaling processes, numerous studies have examined and demonstrated the core role of Shh signaling in maintaining tumor growth and cancer cell survival (12). Vigorous proliferation was observed when the Shh pathway was upregulated in cancer cells, while inhibition of Shh had a suppressing effect (15). All of these phenomena highlight the clinical value of Shh-targeted therapy and the findings of the present study substantiated the theoretical basis for its future application in patients.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Since neoplasms and embryonic development share similar molecular signaling processes, numerous studies have examined and demonstrated the core role of Shh signaling in maintaining tumor growth and cancer cell survival (12). Vigorous proliferation was observed when the Shh pathway was upregulated in cancer cells, while inhibition of Shh had a suppressing effect (15). All of these phenomena highlight the clinical value of Shh-targeted therapy and the findings of the present study substantiated the theoretical basis for its future application in patients.…”
Section: Discussionsupporting
confidence: 74%
“…Numerous lines of evidence have shown aberrant activation of the Shh signaling pathway in cancer patients and drug intervention to block the transduction has resulted in tumor shrinking and cancer cell apoptosis in numerous types of solid tumor (12)(13)(14). In vivo and in vitro, pancreatic cancer cells have a lower proliferative and a higher apoptotic rate after intervention with an Shh antagonist (15,16). Following suppression by a specific inhibitor, malignant hepatic neoplasms also display a reduction in the degree of malignancy, such as slower proliferation and higher vulnerability to chemotherapy (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our lab and elsewhere have provided strong support for the role of CXCR4 and SHH in pancreatic tumor growth, metastasis and desmoplasia by enabling bidirectional tumor-stromal cross-talk (15,17,18,(25)(26)(27). Therefore, we examined the expression status of CXCR4 and SHH in tumor sections by IHC analyses.…”
Section: Hnk Interferes With Tumor-stromal Cross-talk By Downregulatimentioning
confidence: 97%
“…49 Although cross-talk between PSCs and neural elements has not yet been widely studied, recently the effects of cancer cells on neurite outgrowth in the presence and absence of PSCs was assessed. 50 It was found that nerve invasion index and the Dorsal Root Ganglion (DRG) outgrowth index were significantly increased in the presence of PSCs compared with the absence of PSCs. Additionally, the authors further showed that the interaction between cancer cells and neural cells was likely mediated via a paracrine effect of Sonic Hedgehog ligand binding to the receptor Smo on PSCs with subsequent activation of PSCs.…”
Section: Neural Cellsmentioning
confidence: 99%